The possibilities of teaching for, with, and about social justice in a public middle school. Issue 5 (20th October 2018) - Hagerman, Dana; Porath, Suzanne
Abstract: Rolling Hills Middle School has begun the implementation of a personalized learning model with one house of 50 8th grade students. This personalized learning (PL) model promotes collaborative work among groups of students and supports student choice and agency as it fosters learner independence. This qualitative, interpretive case study used student and teacher to focus group data, interviews, classroom observations, and artifacts to document the implementation of PL in its first year. The purpose of this paper is to consider how a personalized, learner-centered environment has authentically led to teaching for, with, and about social justice (Wager, 2008) within the classroom.